2015
DOI: 10.1111/bjet.12345
|View full text |Cite
|
Sign up to set email alerts
|

Social network aided plagiarism detection

Abstract: The prevalence of different kinds of electronic devices and the volume of content on the Web have increased the amount of plagiarism, which is considered an unethical act. If we want to be efficient in the detection and prevention of these acts, we have to improve today's methods of discovering plagiarism. The paper presents a research study where a framework for the improved detection of plagiarism is proposed. The framework focuses on the integration of social network information, information from the Web, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
1
2
0
1
Order By: Relevance
“…At the didactic and scientific level, it has been found that the ethical problem frequently mentioned by teachers is plagiarism, as shown by data of recent studies (Gullifer & Tyson, 2010;Jiang, et al, 2013;Obeid & Hill, 2017;Šprajc et al, 2017), which indicates that "plagiarism" is increasing in higher education. Zrnec and Lavbic (2017) found that plagiarism in higher education was amplified by the use of different types of electronic devices and the amount of content on the Web, as also indicated by the results obtained in the present research. Regarding the relational dimension, the ethical problems mentioned by the university teachers participating in the interview are also found in other research results, such as the difficulties involved in online communication (Capurro & Pingel, 2002) and in the use of personal data (Gupta, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…At the didactic and scientific level, it has been found that the ethical problem frequently mentioned by teachers is plagiarism, as shown by data of recent studies (Gullifer & Tyson, 2010;Jiang, et al, 2013;Obeid & Hill, 2017;Šprajc et al, 2017), which indicates that "plagiarism" is increasing in higher education. Zrnec and Lavbic (2017) found that plagiarism in higher education was amplified by the use of different types of electronic devices and the amount of content on the Web, as also indicated by the results obtained in the present research. Regarding the relational dimension, the ethical problems mentioned by the university teachers participating in the interview are also found in other research results, such as the difficulties involved in online communication (Capurro & Pingel, 2002) and in the use of personal data (Gupta, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…The source code creation process has been considered as a way of reducing the number of false positives [27], as high similarity among submitted programs does not necessarily imply plagiarism and collusion [28]. Many additional hints for raising suspicion can be derived from the process, such as save timestamps [29], resubmission activity [30], classroom seating position [31], and social network [32].…”
Section: Related Workmentioning
confidence: 99%
“…Advances in the visualization of scholarly works, including their exposure to social networking sites, may improve the efficiency of detecting and quantifying plagiarism by emerging electronic gadgets ( 66 ). Ultimately, it is believed that a universal plagiarism detection system of cross-checking submissions to all peer-reviewed journals can minimize the number of retractions due to plagiarism, duplication and simultaneous submissions ( 49 ).…”
Section: Detection Of Plagiarismmentioning
confidence: 99%